Pre-Feasibility Analysis of PV Panel Supported EV Charging Station for Kocaeli University - Tamgacı, Enes Talha; Ünlü, Murat (Düzce Üniversitesi bilim ve teknoloji dergisi (Online), 2025)
While green energy and carbon emission reduction are increasing in importance day by day, the use of renewable energy systems is also increasing. In this context, in line with Kocaeli University's Green Campus goals, the use of renewable energy systems should be increased in our university to increase the energy efficiency of our university and reduce the grid demand. At the same time, the increasing use of electric vehicles increases the number and importance of charging stations. Based on these two important and current subjects, in this study, a preliminary study and analysis of the PV Panel Supported Electric Vehicle Charging Station planned to be installed in 2 regions at Kocaeli University Umuttepe Campus was carried out.